COVID-19 Related Distress Is Associated With Alcohol Problems, Social Media and Food Addiction Symptoms: Insights From the Italian Experience During the Lockdown - Panno, Angelo; Carbone, Giuseppe Alessio; Massullo, Chiara; Farina, Benedetto; Imperatori, Claudio (Frontiers in Psychiatry, 2020)
Background: Several scholars hypothesize that one of the most negative impacts of the coronavirus disease 2019 (COVID-19) crisis would concern the increase of prevalence and severity of both substances and behavioral addiction. Despite the general concerns about the increase of prevalence and severity of addictions related to the COVID-19 emergency, few data are still available. Thus, the main aim of this study was to investigate the association between COVID-19 related distress and: i) alcohol problems, ii) social media addiction (SMA) symptoms, iii) food addiction (FA) symptoms. Methods: A national online-survey was carried out during the Italian lockdown (i.e., 9 March 2020 – 4 May 2020). In the current study, 1,519 participants (365 men and 1154 women, mean age: 28.49±10.89 years) were included. The survey included socio-demographic related items (e.g., age, sex, residential regions, education level, civil status, tobacco use, etc.), as well as ad‐hoc developed questions aimed to investigate COVID-19 related variables (e.g., isolation/quarantine, personal diagnosis to COVID-19, friends or relatives with COVID-19 diagnosis, etc.). Participants also completed the following self-report measures in order to investigate: the psychological impact of COVID-19, alcohol problems, SMA symptoms, FA symptoms and impulsivity. Results: The psychological impact of COVID-19 was independently associated with alcohol problems (β= 0.058, p= 0.043), SMA symptoms (β= 0.259, p< 0.001) and FA symptoms (β= 0.150, p< 0.001). Conclusion: Taken together, our results seem to confirm the general concerns about the negative impacts of the COVID-19 emergency on addictive behaviors, suggesting that this issue should be carefully monitored.